The dynamic value of MNE political embeddedness: The case of the Chinese automobile industry - Sun, Pei; Mellahi, Kamel; Thun, Eric (Journal of International Business Studies, 2010)
This paper examines the complex relationship between the embeddedness of multinational enterprises (MNEs) in host-country political networks and their long-run competitive positions in host emerging markets. We report the findings of a longitudinal study of the Chinese automobile sector from the early 1980s to the mid 2000s. Using data from 142 interviews over 11 years, and a wide range of secondary sources, we explore the process through which the value of political embeddedness changed over time in the face of profound and rapid changes in host-country business environments. On the basis of this longitudinal study, the paper unravels the underlying mechanisms that lead to the declining, and even negative, value of deep political embeddedness by MNEs in a politically stable emerging economy.